Tunicamycin inhibits ganglioside biosynthesis in rat liver Golgi apparatus by blocking sugar nucleotide transport across the membrane vesicles. - Yusuf, H K (1983)
The synthesis of ganglioside GM1 in intact rat liver Golgi-derived vesicles is stimulated by phosphatidylglycerol as much (about 20-fold) as by Triton X-100. The antibiotic tunicamycin inhibits strongly the synthesis, in the presence as well as in the absence of the phospholipid, but has no effect when Golgi membranes are solubilized with detergent. In Pronase-treated Golgi vesicles, which retain full enzyme activity, both phospholipid dependence and tunicamycin inhibition of the synthesis disappear completely. When freshly prepared Golgi vesicles are incubated with 125 microM UDP-[3H]Gal for 10 min at 30 degrees C, the nucleotide sugar is found to be transported into the vesicles at an approximate rate of about 85 pmol/mg of protein per min, 92% of which remains firmly bound to the membrane. Tunicamycin inhibits this transport in a concentration-dependent manner. These results indicate the existence of carrier proteins in rat liver Golgi vesicles, which mediate the transport of the sugar nucleotide UDP-Gal, and that the carriers face the cytoplasmic side of the vesicles. The results also show that, although the mechanism of phosphatidylglycerol-induced stimulation of the synthetic activity remains unclear, tunicamycin inhibits ganglioside biosynthesis by blocking the transport of the nucleotide sugar and not by inhibiting the transferase directly.